Drought intensity and frequency have contrasting effects on development time and survival of the green spruce aphid. (2nd March 2015) - Banfield‐Zanin, Jennifer A.; Leather, Simon R.
Abstract Elatobium abietinum (Walker) is the most important defoliating pest of Sitka spruce Picea sitchensis (Bong.) Carr. Climate change in the U.K. is predicted to increase incidences of spring–summer drought events, with the aphid expected to respond to these changes. This will have serious implications for damage levels and growth of infested Sitka spruce, as well as control of the aphid pest. Under controlled laboratory conditions, nymphal survival rate, lifespan and generation time of E. abietinum were examined in time‐staggered trials during the spring and autumn periods of population growth, using five levels of drought with differing frequencies and magnitude. Survivorship and lifespan were unaffected by drought stress compared with a well‐watered control. Generation time, however, was increased under severe continuous and high amplitude intermittent drought stress. Advancement of Sitka spruce dormancy was not supported as no differences between the autumn trials were observed for the three parameters. The findings of the present study suggest that, under severe water deficit, populations of E. abietinum may be reduced as a result of a reduced period of time available for reproduction. This has implications for the population development of E. abietinum and, consequently, damage levels and growth reductions of host Sitka spruce under altered climatic conditions.